Esports consumer perspectives on match-fixing: implications for gambling awareness and game integrity. Issue 2 (4th May 2019) - Abarbanel, Brett; Johnson, Mark R.
ABSTRACT: This article examines consumer perspectives on match-fixing in esports – professionalized competitive video game play – and the implications of these perspectives for understanding game and gambling integrity. The relationship between match-fixing, game integrity and gambling is a close one, as gambling markets are reliant on strong game integrity, but has not yet been studied in detail in the context of esports. Drawing on extensive qualitative data collected from esports fans around the world, this article examines perceptions of gambling awareness, integrity and esports gambling to assess esports consumers' awareness of and attitudes towards gambling-related match-fixing. Results indicate that esports viewers are not deeply concerned by match-fixing. In addition, spectators typically view gambling as a cause of corruption among competitors, but also understand and accept some elements of the practice. Further, spectators tend to rely on rules to determine their assessment of what is 'wrong', rather than assessments based on ethics, and are often willing to forgive infractions through a range of reasons and justifications. We propose a need for education among esports spectators, extending existing anti-cheating programmes beyond just athletes to include the broader esports community.